2018
DOI: 10.1536/ihj.17-146
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Risk Factors, and Outcomes of Hyperlactatemia after Heart Transplantation

Abstract: SummaryHyperlactatemia (HL) is associated with tissue hypoperfusion during cardiac surgery, which results in postoperative morbidity and mortality among patients undergoing cardiopulmonary bypass surgery. The aim of this study was to determine the incidence, risk factors, and outcome of HL after heart transplantation (HTx) in one of the largest Japanese single-center cohorts. We retrospectively studied the lactate levels in 49 patients who underwent HTx at the University of Tokyo Hospital from August 1, 2010 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…In the presented research, hyperlactatemia was considered with the of >1.6 mmol/l, same as it is for other cardiac surgeries and non-surgical patients in our center. Despite the initially emerging pattern with early peak of the lactate values, that was similar to other post-HTX lactate analyses (Hsu et al, 2015;Hoshino, Kinoshita & Ono, 2018), more detailed evaluation revealed various serum lactate level trends. The interpretation of the initial results indicates the increase to the highest serum lactate level within first 6 postoperative hours with subsequent gradual decrease (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the presented research, hyperlactatemia was considered with the of >1.6 mmol/l, same as it is for other cardiac surgeries and non-surgical patients in our center. Despite the initially emerging pattern with early peak of the lactate values, that was similar to other post-HTX lactate analyses (Hsu et al, 2015;Hoshino, Kinoshita & Ono, 2018), more detailed evaluation revealed various serum lactate level trends. The interpretation of the initial results indicates the increase to the highest serum lactate level within first 6 postoperative hours with subsequent gradual decrease (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Under anaerobic conditions, cellular metabolism converts pyruvate to lactate. Therefore, serum lactate levels relate to the oxygen debt and correspond with the severity of tissue hypoperfusion (Adeva-Andany et al, 2014;Hoshino, Kinoshita & Ono, 2018). The normal plasma lactate concentration for ABG is reported from 0.3 to 1.6 mmol/L (Broder & Weil, 1964), whereas lactic acidosis is generally defined with a threshold of greater than four mmol/L, even in the absence of overt acidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate studies in surgical patients usually appear in cardiac procedures. In the analysis of the risk factors for lactate elevation in this patient group of Hoshino et al, 11 operative time was not significant (p = 0.439. In contrast, in the study of Wu et al 12 the operative time was closely related to severe hyperlactatemia (p = 0.016).…”
Section: Discussionmentioning
confidence: 69%
“…16) According to data from a Japanese center with an annual volume of over 10 transplants, there was no in-hospital mortality after HT. 17) However, there are no requirements/regulations with regards to institutional performance in organ transplantation in Korea. Given the recent increase in HTs performed in Korea, 18) the association between HT case-volume and posttransplant mortality was analyzed using data from the National Health Insurance Service (NHIS) of Korea to see if the same relationship holds and if minimal performance requirements would be beneficial.…”
mentioning
confidence: 99%